Hack the cybersecurity interview - Foulon, Christophe; Underhill, Ken; Hopkins, Tia (Expert insight, 2024)
The cybersecurity field is evolving rapidly, and so are the interviews for cybersecurity roles. Hack the Cybersecurity Interview, Second Edition, is the essential guide for anyone aiming to navigate this changing landscape. This edition, updated and expanded, addresses how to fi nd cybersecurity jobs in tough job markets and expands upon the original cybersecurity career paths. It offers invaluable insights into various cybersecurity roles, such as cybersecurity engineer, penetration tester, cybersecurity product manager, and cybersecurity project manager, focusing on succeeding in interviews. This book stands out with its real-world approach, expert insights, and practical tips. It's not just a preparation guide; it's your key to unlocking success in the highly competitive field of cybersecurity. By the end of this book, you will be able to answer behavioural and technical questions and effectively demonstrate your cybersecurity knowledge.